Sidewalk story - Mathis, Sharon Bell. (New York : Puffin Books, 1986)
When her best friend's family is evicted from their apartment, a nine year-old black girl decides to do something about the situation.
Illustrator on title page is a misprint. Includes no illustrations.
Book Links (A.L.A.).
Booklist.
Wilson's Children.
4.8
3-6
Keywords: African Americans -- Fiction; Friendship -- Fiction; African Americans -- Fiction; Friendship -- Fiction